Dianetics the original thesis - Hubbard, L. Ron (La Fayette Ron), 1911-1986 (Los Angeles, California Bridge Publications, Inc., 2007)
According to the publisher, this book presents the bedrock foundation of Dianetic discoveries : the original axioms, the dynamic principle of existence, the anatomy of the analytical and reactive mind, the dynamics, the tone scale, the auditor's code, and the first description of a clear. Also included is a description of the author's beliefs regarding "auditing"
Discoveries and principles. Primary axioms ; An analogy of the mind ; The dynamics ; The basic individual ; Engrams ; Aberrations ; The tone scale ; The character of engrams -- Auditing. The auditor's code ; Auditing ; Diagnosis ; Exhaustion of engrams ; The analyzer ; The clear -- Clearing. Engram chains ; Dramatization ; Prenatal, birth and infant engrams ; The "laws" of returning
A Hubbard publication
Includes bibliographical references
Donated by Hubbard Publication 10/11/16
Keywords: Dianetics